Employee Performance Management System (EPMS) And Lecturers’ Organisational Commitment In Higher Education Institutions In Saudi Arabia: The Moderating Role Of Change Agents And The Mediating Role Of Lecturers’ Satisfaction - Alanazi, Farhan (2018)
The overarching aim of the study is to assess the Employee Performance Management System (EPMS) and Lecturers‘ Organisational Commitment in Higher Education Institutions in Saudi Arabia: the Moderating Role of Change Agents and the Mediating Role of Lecturers Satisfaction. The study utilized quantitative and qualitative methods. Apparently, the highest importance of predictor affected the employment performance was observed with change agent (59%), followed by staff organization commitment (28%), level of satisfaction (10%) and field of study (3%). While the highest importance of predictor affected the staff organization commitment was observed with level of satisfaction (40%), followed by employment performance management system (30%) and change agent (30%).